2004
DOI: 10.1249/01.mss.0000139795.83030.d1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sequential Bouts of Resistance Exercise on Androgen Receptor Expression

Abstract: Three sequential bouts of heavy resistance exercise increases serum TST and are effective at up-regulating AR mRNA and protein expression that appears to correspond to subsequent increases in myofibrillar protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
69
1
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 26 publications
4
69
1
8
Order By: Relevance
“…These results coincided with those of previous studies [7][8][9][10] and suggest that site-specific muscle loss of the thigh was observed in the present sample. Furthermore, the QF:HM ratio was positively associated with the duration of vigorous exercise during daytime physical activities.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…These results coincided with those of previous studies [7][8][9][10] and suggest that site-specific muscle loss of the thigh was observed in the present sample. Furthermore, the QF:HM ratio was positively associated with the duration of vigorous exercise during daytime physical activities.…”
Section: Discussionsupporting
confidence: 94%
“…Interestingly, in the anterior and posterior regions of the thigh, age-related muscle loss was observed in the quadriceps but not in the hamstrings and adductors. 8 The etiology of sitespecific sarcopenia is multifactorial and complex. Several factors have been implicated such as declining anabolic hormone concentrations, nutritional deficiencies, chronic inflammation, and insulin resistance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Androgen receptor mRNA and protein have been observed to increase after 1-3 strength training sessions where levels of serum testosterone was acutely elevated (Bamman et al 2001;Willoughby and Taylor 2004;Hulmi et al 2008;Spiering et al 2009). Furthermore, administration of testosterone (without strength training) increases the content of androgen receptors in animal muscles (Carson et al 2002;Lee et al 2003) and humans (Ferrando et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, increases in resting testosterone levels were not observed in middle-aged (Cadore et al 2008a) or elderly people (HĂ€kkinen et al, 2000(HĂ€kkinen et al, , 2001aKraemer et al, 1999). Chronic adaptations to ST apparently occur at the level of cellular androgen receptors (ARs), given that ARs present on muscle cells seem to increase in number in response to this type of training (Inoue et al, 1994;Willoughby & Taylor, 2004), and this adaptation may result in improved hormone-receptor interaction (Bamman et al, 2001;Willoughby & Taylor, 2004). Conversely, reductions in testosterone levels associated with increases in cortisol levels have been observed in response to aerobic training in athletes subjected to high-volume training (MaĂŻmoun et al, 2003).…”
Section: Introductionmentioning
confidence: 99%